2022
DOI: 10.1007/s10654-022-00842-z
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity, diabetes, lifestyle factors and risk of gastroesophageal reflux disease: a Mendelian randomization study

Abstract: Adiposity, diabetes, and lifestyle factors are linked to gastroesophageal reflux disease (GERD) in observational studies. We conducted a two-sample Mendelian randomization analysis to determine whether those associations are causal. Independent genetic variants associated with body mass index (BMI), waist circumference (with and without adjustment for BMI), type 2 diabetes, smoking, and alcohol, coffee and caffeine consumption at the genome-wide significance level were selected as instrumental variables. Summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 38 publications
7
47
0
10
Order By: Relevance
“…Previous MR studies examined the causal associations between smoking initiation, asthma, type 2 diabetes, BMI, waist circumference, waist-to-hip ratio, standing height, and the risk of GORD primarily among European-ancestry individuals in the UKB database ( 16 , 35 37 ), whose MR findings were also replicated in this study with larger-scale GORD GWAS datasets from Neale Lab and FinnGen consortium. In this study, we systematically examined causal associations between 66 exposures across 6 modifiable pathways and the risk of GORD in order to comprehensively elucidate the causal modifiable factors that were associated with the risk of GORD.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Previous MR studies examined the causal associations between smoking initiation, asthma, type 2 diabetes, BMI, waist circumference, waist-to-hip ratio, standing height, and the risk of GORD primarily among European-ancestry individuals in the UKB database ( 16 , 35 37 ), whose MR findings were also replicated in this study with larger-scale GORD GWAS datasets from Neale Lab and FinnGen consortium. In this study, we systematically examined causal associations between 66 exposures across 6 modifiable pathways and the risk of GORD in order to comprehensively elucidate the causal modifiable factors that were associated with the risk of GORD.…”
Section: Discussionsupporting
confidence: 54%
“…Thirdly, genetic variants associated with specific exposures will index lifetime differences and thus produce causal estimates that are unsusceptible to the attenuation by errors (regression dilution bias) ( 15 ). To date, central obesity indicators (BMI, waist circumference, hip circumference) and daily habits (smoking and alcohol consumption) have been examined for their causal effects on the risk of GORD using MR analysis ( 16 ). However, there have been no studies evaluating factors that are causally associated with the risk of GORD as comprehensively as possible.…”
Section: Introductionmentioning
confidence: 99%
“…After exclusion of studies using overlapping or same outcome data, 29 articles based on non-overlapping populations were eligible for inclusion in one or more meta-analyses. The number of studies included in each outcome category was seven for circulatory system diseases, 4 , 5 , 6 , 7 , 8 , 9 , 10 six for digestive system diseases, 11 , 12 , 13 , 14 , 15 , 16 six for nervous system diseases, 17 , 18 , 19 , 20 , 21 three for musculoskeletal system outcomes, 22 , 23 , 24 two for endocrine and metabolic diseases, 25 , 26 two for eye diseases, 27 , 28 and four for neoplasms. 29 , 30 , 31 , 32 In addition to the included studies, 123 de novo MR analyses ( n =51 for smoking initiation, n = 72 for lifetime smoking) were conducted.…”
Section: Resultsmentioning
confidence: 99%
“…During the last few years, the potential causal association between smoking and risk of different diseases has been investigated using the Mendelian randomization (MR) approach. 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 MR is a method that utilizes genetic variants associated with a difference in the exposure (e.g., smoking liability) as instrumental variable for the exposure to determine the causal role of the exposure in the development of disease. 33 The MR design mitigates confounding because genetic alleles are randomly allocated when passed from parents to offspring and therefore usually not related to other risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Since genetic variants are randomly assorted at conception and cannot be modified by the onset of disease, MR investigation is less likely to be affected by confounding and reverse causality. Even though previous MR studies identified the associations of adulthood body mass index (BMI) and waist-hip ratio (WHR) with the risk of gastroesophageal reflux, esophageal cancer, gastric cancer, diverticular disease, non-alcoholic liver disease, liver cancer, cholelithiasis, and pancreatic cancer (15)(16)(17)(18), the MR associations of adulthood obesity with other gastrointestinal diseases, like peptic ulcer, irritable bowel syndrome and pancreatitis, remains unestablished. In addition, the associations of other obesity-related traits with the risk of gastrointestinal disease have not been scarcely investigated.…”
Section: Introductionmentioning
confidence: 99%